The Method for Static Composting Treatment of the Landscaping Waste - An, Liwei (Frontiers in Energy Research, 2020)
In order to speed up the process of landscape garbage composting and reduce environmental pollution, the static composting method of landscape garbage was studied in depth. The spring landscape garbage in Beijing Xiangshan Park was used as the main raw material, and an appropriate amount of dried chicken manure was added for high-temperature composting experiments. Furfural residue was added to landscape waste compost, and the dynamic changes of compost quality, total nitrogen, carbon-nitrogen ratio, and plant inhibitors were studied. Through orthogonal experiments, chicken manure was used as a C / N regulator, and bacteria and wood vinegar were used as additives. The total volume of each treatment, changes in pH and EC values, and seed germination index were analyzed and compared. The results show that this method reduces the bulk density of 39 mg / kg, increases the total porosity by 11.6%, and increases the water holding porosity by 7.74%, which can significantly increase the N, P, and K content of landscape waste compost products and reduce the product. The bulk density of the fertilizer has increased the total porosity and water holding porosity of the fertilizer, and the quality of the fertilizer has been significantly improved.